2018
DOI: 10.17586/2220-8054-2018-9-3-335-341
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically tunable viscoelastic response of soft magnetic nanocomposites with wormlike surfactant micellar matrix

Abstract: Magnetorheological effects in viscoelastic soft magnetic nanocomposites (SMNs) composed of submicron magnetite particles embedded in a network of wormlike micelles (WLMs) of surfactant were studied in a homogeneous magnetic field. In field, the SMNs showed rapid rise of storage and loss moduli by a few orders of magnitude as a result of the ordering of magnetized particles into chain-like or columnar structures.Moreover, solid-like behavior and yield stress of the SMNs were observed. Study of rheological respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Very small nanoparticles around 3 nm in diameter were shown to have no effect on viscosity in WLM solutions, though they incorporate into micellar chains as pearl-necklace structures. 49 Meanwhile, for anionic WLMs of sodium oleate and octyl trimethylammonium bromide mixed with negatively charged silica, zero-shear viscosity increased 5-fold when particle size decreased from 60 to 15 nm. Clearly particle size impacts pseudo-cross-linking and rheology, but the mechanisms at different dimensions are not yet fully characterized.…”
Section: Effect Of Particle Concentrationmentioning
confidence: 97%
“…Very small nanoparticles around 3 nm in diameter were shown to have no effect on viscosity in WLM solutions, though they incorporate into micellar chains as pearl-necklace structures. 49 Meanwhile, for anionic WLMs of sodium oleate and octyl trimethylammonium bromide mixed with negatively charged silica, zero-shear viscosity increased 5-fold when particle size decreased from 60 to 15 nm. Clearly particle size impacts pseudo-cross-linking and rheology, but the mechanisms at different dimensions are not yet fully characterized.…”
Section: Effect Of Particle Concentrationmentioning
confidence: 97%
“…7(a), it is seen that the disruption of the network is faster than the recovery. Gradual growth of the storage modulus takes tens of the seconds that is close to the typical relaxation time for the WLM networks [20,25]. Such restoring rate is comparable to the restoring rate of various injectable systems for wound healing application [5].…”
Section: Recovery Testmentioning
confidence: 99%
“…Properties of the WLM network can be modified by nanoparticles. Until now, only spherical inorganic particles were dispersed within WLM network [14][15][16][17][18][19][20]. It was shown that these particles can significantly increase the rheological properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations